Data Literacy and Logical Reasoning: A New Foundation for STEM Education in the Age of Information Abundance - Muhammad Hasbi; Harling Danil; Sri Verlin; Hardi Yanti (Jurnal Riset dan Inovasi Pembelajaran, 2026)
In the era of information abundance, students frequently encounter “cognitive disruptions” or logical fallacies when synthesizing scientific conclusions. This challenge is particularly pronounced within the Madrasah educational environment, where a critical need exists to bridge traditional verification values with contemporary data literacy. This study evaluates the effectiveness of synergizing data literacy and logical reasoning as a foundational framework for STEM education at Madrasah As’adiyah Pompanua, aiming to enhance students’ cognitive capacity in formulating valid scientific arguments. Employing a quantitative quasi-experimental design, this research involved two student cohorts. Data were collected through assessments of data literacy and the Test of Logical Thinking (TOLT), then analyzed using descriptive statistics, ANCOVA, and Normalized Gain (N-Gain) analysis. The findings demonstrate that integrating data literacy and logical reasoning significantly improves STEM educational outcomes. The experimental group attained a mean score of 81.30, substantially outperforming the control group’s 62.55. Data literacy was found to sharpen cognitive acuity by establishing an empirical foundation that minimizes logical gaps. The model’s high efficacy is evidenced by an N-Gain value of 0.71, signifying a pedagogical shift from passive knowledge acquisition to critical analysis. This research contributes to the evolution of STEM models in Islamic educational settings by demonstrating that indigenous values, such as the principle of verification (tabayyun), serve as potent catalysts for adopting data literacy. Practically, this study provides a strategic framework for educators to implement evidence-based learning, ensuring students possess the essential analytical competencies required to navigate the complexities of the digital age.